Pengaruh Harga, Diskon dan Ulasan Produk Terhadap Keputusan Pembelian Konsumen di Marketplace - Fitrotul Mukaromah; Herma Artika Putri; Jessica Valentina Darwis; Lulu Il Mufidah; Fikri Rizki Utama (Indo Publishing, 2025)
The development of digital technology has shifted people's shopping behavior from conventional systems towards marketplace-based transactions. Competition among business actors emphasizes the importance of digital marketing strategies to attract consumer interest in the purchasing process. This study aims to analyze the influence of price, discounts, and product reviews on consumer purchasing decisions in the marketplace. The research method uses a quantitative approach with a survey technique through a questionnaire distributed to 100 respondents who actively shop on the Shopee, Tokopedia, Lazada, and TikTok Shop platforms. Data analysis was performed using multiple linear regression through IBM SPSS Statistics version 27. The results show that price and product reviews have a positive and significant influence on purchasing decisions, while discounts do not have a significant influence. Simultaneously, these three variables are proven to have a significant influence on purchasing decisions. These findings indicate that accurate digital information in the form of consumer reviews and competitive pricing are more decisive in purchasing decisions than discounts. This study provides implications for business actors and marketplace platforms to enhance the credibility of the review system and design pricing strategies that align with consumer preferences within the e-commerce ecosystem.